Back flux during anaerobic oxidation of butane supports archaea-mediated alkanogenesis - Song-Can Chen; Sheng Chen; Niculina Musat; Steffen Kümmel; Jiaheng Ji; Marie Braad Lund; Alexis Gilbert; Oliver J. Lechtenfeld; Hans-Hermann Richnow; Florin Musat (Nature Communications)
Abstract Microbial formation and oxidation of volatile alkanes in anoxic environments significantly impacts biogeochemical cycles on Earth. The discovery of archaea oxidizing volatile alkanes via deeply branching methyl-coenzyme M reductase variants, dubbed alkyl-CoM reductases (ACR), prompted the hypothesis of archaea-catalysed alkane formation in nature (alkanogenesis). A combination of metabolic modelling, anaerobic physiology assays, and isotope labeling of Candidatus Syntrophoarchaeum archaea catalyzing the anaerobic oxidation of butane (AOB) show a back flux of CO2 to butane, demonstrating reversibility of the entire AOB pathway. Back fluxes correlate with thermodynamics and kinetics of the archaeal catabolic system. AOB reversibility supports a biological formation of butane, and generally of higher volatile alkanes, helping to explain the presence of isotopically light alkanes and deeply branching ACR genes in sedimentary basins isolated from gas reservoirs.